Self-Oscillating Parametric Optical Frequency Comb Generation Using an Electroabsorption Modulated Laser-Based Optoelectronic Oscillator - Yumin Cheng; Juanjuan Yan; Siyu Zhao (IEEE Photonics Journal, 2019)
A scheme for parametric optical frequency comb (OFC) generation using an electroabsorption modulated laser (EML) based optoelectronic oscillator is proposed and experimentally demonstrated. A phase modulator is cascaded with EML in the oscillating loop. In addition, the phase modulated laser is used as pump seeds for the parametric frequency mixer. In the mixer, a 100-m single-mode fiber is employed to compress the pump pulses, and the parametric process is stimulated in a 200-m-high nonlinear fiber (HNLF) with flat normal dispersion. In our experiments, a 10-GHz radio frequency signal with a side-mode suppression radio of 47 dB and a single-sideband phase noise of −109.89 dBc/Hz at 10 kHz offset is obtained. When the pump power injected into HNLF is 28 dBm, a 10-tone parametric OFC with a 5-dB power variation and spacing equal to the oscillation frequency is generated.